2019
DOI: 10.1101/784926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Abnormal vertebral patterns in genetically heterogeneous deceased fetuses and neonates: evidence of selection against variations”

Abstract: ObjectiveTo assess the vertebral pattern in a cohort of deceased fetuses and neonates, and to study the possible impact of DNA Copy Number Variations (CNVs) in coding regions and/or disturbing enhancers on the development of the vertebral pattern.MethodRadiographs of 445 fetuses and infants, deceased between 2009 and 2015, were assessed. Terminations of pregnancies, stillbirths and neonatal deaths were included. Patients were excluded if the vertebral pattern could not be determined. Copy number profiles of 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Recent biological and genetic studies, however, indicate that the cervical rib in early childhood is identified, in mice and in humans, as positively and significantly associated with the most frequent congenital anomalies, and several severe medical conditions [Table 5 ( Adson & Coffey 1927;Gladstone and Wakeley, 1932;Bagnall et al 1984;McNally et al 1990;Schumacher et al 1992;Keeling and Kjaer, 1999;Galis et al 2006;Bots et al 2011;Castori et al 2016, Schut et al 2019a2019b)].…”
Section: H 3 the Cervical Rib During Early Childhood A 'Morbidity Criterion'mentioning
confidence: 99%
“…Recent biological and genetic studies, however, indicate that the cervical rib in early childhood is identified, in mice and in humans, as positively and significantly associated with the most frequent congenital anomalies, and several severe medical conditions [Table 5 ( Adson & Coffey 1927;Gladstone and Wakeley, 1932;Bagnall et al 1984;McNally et al 1990;Schumacher et al 1992;Keeling and Kjaer, 1999;Galis et al 2006;Bots et al 2011;Castori et al 2016, Schut et al 2019a2019b)].…”
Section: H 3 the Cervical Rib During Early Childhood A 'Morbidity Criterion'mentioning
confidence: 99%